PENGETAHUAN HARTA BENDA PERKAWINAN AKIBAT PERCERAIAN - Wahyuni Retnowulandari (Universitas Trisakti, 2020)
The divorce trend in Indonesia is increasing every year. In 2018, Indonesia's divorce rate reached 408,202 cases, an increase of 9% compared to the previous year. The biggest causes of divorce in 2018 were disputes and ongoing bickering with 183,085 cases. Economic factors rank second with 110,909 cases, while other problems are husband / wife leaving (17.55%), domestic violence (2.15%), and drunkenness (0.85%). The phenomena resulting from divorce are generally inconsistencies in child care or seizure of marital property. Therefore, in an effort to overcome the continuing increase in divorce in society and disputes due to the breakdown of marriage, it is necessary to provide counseling to the prospective bride and groom regarding the marriage law, KHI and also for those who have been married for a long time need to be reminded again about the rights and obligations of married couples with outreach to the community of Duri Kosambi Village, Kec. Cengkareng, West Jakarta, which is around the Trisakti University campus. The implementation method used was normative and descriptive extension, which was then analyzed qualitatively by using feminist theory of jurisprudence in explaining and answering questions, and opening legal aid posts. The results of the PKM implementation were quite successful considering that 70% of the participants who attended asked about the participants' personal cases in the question and answer session and at the legal aid post were able to understand that the arrangement for the distribution of marital assets due to divorce was not always fair, especially in the case of marital assets from women. Therefore, cases related to the distribution of marital assets do not always have to be the same, but study cases and divide proportionally so that they are gender equitable.